ISLAMIC ECOTHEOLOGY: UNDERSTANDING THE CONCEPT OF KHALIFAH AND THE ETHICAL RESPONSIBILITY OF THE ENVIRONMENT - Aulia Rakhmat (Academic Journal of Islamic Principles and Philosophy, 2022)
This paper discusses the relationship between Islamic theology and environmental ethics. Based on the development of the discourse on an environmental problem that arises in the public sphere, Islamic theology as the divine discourse is required to participate in overcoming it at the conceptual level starting from the relationship between humans and the environment. The concept of human in Islamic theological discourse is defined as the center of universal consciousness through the concept of the vicegerent of God on earth (khalifatullah fil ard). Such a concept is often misunderstood as the legitimization of the supremacy of human power over other creatures on earth (anthropocentrism). Therefore, the objective of the study is to enrich studies on Islamic Eco-theology, especially related to the concept of khalifa and its relation with responsibility towards nature. To conduct the research, this paper applied an intertextual approach to extract and reveal the meaning of khalifa and its relation with responsibility in classical Muslim works of tafsir, philosophy, theology, Sufism, and theosophy. The result of the discussion shows that the meaning of humans as the vicegerent of God in the world is not the legitimacy of total mastery but a responsibility that must be fulfilled.